Conceptions of Time Travel in Literature for Children and Young Adults Three Case Studies - Planka, Sabine (Journal for Religion, Film and Media, 2024)
This article explores the motif of time travel in children’s and young adult literature. After a brief overview of the origins and development of this motif, the article focuses on three books: Todd Strasser’s The Beast of Cretacea (2015), Alex Scarrow’s TimeRiders (2010), and Torben Kuhlmann’s all-age picture book Einstein. The Fantastic Journey of a Mouse Through Space and Time (2021). While the time travel in all three books requires technical equipment, the reasons for undertaking this travel differ, connected to various topics that affect the readers. Time travel is evidently a flexible and adaptable motif. As the article shows, it can be connected to memory studies.